Exploring resilience mechanism in learning burnout among pupils: school adjustment and academic self-efficacy - Jiang, Changcheng; Gao, Qiufeng (Frontiers in Psychology, 2025)
IntroductionThe conceptualization and protective mechanisms of resilience may differ across age groups, leaving the underlying processes of resilience against learning burnout among pupils largely unexplored. According to Kumpfer’ s resilience framework, resilience in pupils depends on the successful adaptation of resiliency characteristics (e.g., academic self-efficacy) to their environment (e.g., school adjustment).MethodsTo examine the mediating roles of both factors, 413 pupils (49.6% male; M = 10.81, SD = 0.72) from Shenzhen, China, participated. SEM with bootstrapping was used to test the mediation model.Results(1) consistent with findings in older students, school adjustment mediated the relationship between resilience and learning burnout; (2) In contrast to older students, academic self-efficacy did not function as an independent mediator, as it did not significantly predict learning burnout. Instead, it exerted its protective effect indirectly through a sequential pathway involving school adjustment.ConclusionThese findings suggest that pupils’ resilience may rely more on the school, with academic self-efficacy buffering learning burnout only when it supports adaptive functioning in school. Early interventions that strengthen internal resources and promote constructive school adjustment may thus help mitigate learning burnout in this age group.